Role of Ayurvedic Modalities in the Management of Ekakustha (Psoriasis) ) : A Case Report - Moniruzzaman, M d; Akbar, Waquar; KarMahapatra, P B (International Research Journal of Ayurveda & Yoga, 2021)
Psoriasis is a chronic papulo-squamous disorder of unknown aetiology characterized by well-defined erythematous papules and plaque lesions with silvery white micaceous scales. It is an incurable ailment which is frustrating to the suffering human physically as well as psychologically. There is no such satisfactory safe and curable remedy in modern medicine. Ayurveda has considered all skin diseases under Kustha. Ekakustha (Psoriasis)is one of the kshudra kusthas characterized by Aswedan (absence of perspiration), Mahavastu (big size lesions), Matsyashakalapam (fishlike scale). Due to similarity of sign and symptoms Ekakustha(Psoriasis) may be correlated with Psoriasis. In the present study, a diagnosed case of psoriasis has been treated with ayurvedic modalities like Deepan –pachan (appetizer-digestives), Ghritapana (intake of medicated ghee), Virechana (purgation) as sodhana(purification), Shamana (pacification) yoga and Takradhara. The effectiveness of these treatments were found unique and very much satisfactory. ‘PASI’ (Psoriasis area and Severity index) score was taken as assessment parameter of improvement. The skin lesions of the patient was calculated by ‘PASI’ score before starting the treatment, was found to be 48, which decreased to 1.2 at the end of treatment .This case report showed remarkable improvement in overall condition of the patient with no recurrence since 1 year.